Pregnancy-associated plasma protein A – a new indicator of pulmonary vascular remodeling in chronic thromboembolic pulmonary hypertension? - Kriechbaum, Steffen D.; Rudolph, Felix; Wiedenroth, Christoph B.; Mielzarek, Lisa; Haas, Moritz; Guth, Stefan; Hamm, Christian W.; Mayer, Eckhard; Liebetrau, Christoph; Keller, Till; Justus Liebig University Giessen (My University, 2020)
Background: In chronic thromboembolic pulmonary hypertension (CTEPH) impaired pulmonary hemodynamics lead to right heart failure. Natriuretic peptides reflect hemodynamic disease severity. Pregnancy-associated plasma protein-A (PAPP-A) might address another aspect of CTEPH - chronic tissue injury and inflammation. This study assessed dynamics of PAPP-A in CTEPH patients who undergo therapy with pulmonary endarterectomy (PEA) or balloon pulmonary angioplasty (BPA). Methods: The study included a total of 125 CTEPH patients scheduled for treatment (55 PEA/ 70 BPA) and a control group of 58 patients with pulmonary hypertension other than CTEPH. Biomarker measurement was performed at baseline and follow-up in the CTEPH cohort, prior to each BPA in the BPA cohort and once in the control group. Results: The median PAPP-A level was slightly higher (p = 0.05) in CTEPH patients [13.8 (11.0–18.6) mU/L], than in the control group [12.6 (8.6–16.5) mU/L], without a difference between the BPA and PEA group (p = 0.437) and without a correlation to mean pulmonary artery pressure (p = 0.188), pulmonary vascular resistance (p = 0.893), cardiac index (p = 0.821) and right atrial pressure (p = 0.596). PEA and BPA therapy decreased the mean pulmonary artery pressure (p < 0.001) and pulmonary vascular resistance (p < 0.001) and improved the WHO-functional-class (baseline: I:0/II:25/III:80/IV:20 vs. follow-up: I:55/II:58/III:10/IV:2). PAPP-A levels decreased after PEA [13.5 (9.5–17.5) vs. 11.3 (9.8–13.6) mU/L; p = 0.003) and BPA treatment [14.3 (11.2–18.9) vs. 11.1 (9.7–13.3) mU/L; p < 0.001). The decrease of PAPP-A levels is delayed in comparison to N-terminal pro-B-type natriuretic peptide. Conclusion: PAPP-A is overexpressed in CTEPH and decrease significantly after surgical or interventional therapy, however without association to hemodynamics. Further investigation is needed to define the underlying mechanism of PAPP-A expression and changes after therapy in CTEPH.
Keywords: PAPP-A; Pregnancy-associated plasma protein A; Pappalysin-1; BPA; PEA; CTEPH; Vascular remodeling; ddc:610